HUMAN RESOURCE COMPETENCE DEVELOPMENT MODEL IN BANDUNG CITY TOURISM AS AN ATTEMPT TO IMPROVE THE COMPETITIVENESS OF TOURISM SECTOR - Rofaida, Rofi (ASEAN Journal on Hospitality and Tourism, 2015)
The development of tourism sector is closely related to the improvement of hotel and restaurant industry. Its contributions to PDRB, employment, and the increasing business entity show that the economic activity in this sector remains high and becomes superior in Bandung city. Nevertheless, the problem existed is related with the mismatch between the competence owned by the human resource and the industry requirement. The aim of the study are (1) developing strategy to improve the human resource competence in hotel and restaurant sector based on gap analysis between the required human resource competence profile and provided human resource competence profile.(2) Mapping and analyzing the role of ‘triple helix’ system (industry, government, and academician) in constructing human resource competence development model. The result of the study in front office, housekeeping, waiter, and cook show that the competence owned have not fulfilled the SKKNI standard in Hotel and Restaurant. Strategies proposed by this study are: (1) Improving training institution capacity. (2) Developing human resource competence through training and (3) Developing human resource through certification and standardization. Developing human resource competence is determined by three factors: industry, government policy, and education institution. Mapping and analyzing the role of ‘triple helix’ system (industry, government, and academician) will develop human resource competence development model in hotel and restaurant sector